2014
DOI: 10.1038/mt.2013.219
|View full text |Cite
|
Sign up to set email alerts
|

Tissues in Different Anatomical Sites Can Sculpt and Vary the Tumor Microenvironment to Affect Responses to Therapy

Abstract: The tumor microenvironment can promote tumor growth and reduce treatment efficacy. Tumors can occur in many sites in the body, but how surrounding normal tissues at different anatomical sites affect tumor microenvironments and their subsequent response to therapy is not known.We demonstrated that tumors from renal, colon, or prostate cell lines in orthotopic locations responded to immunotherapy consisting of three agonist antibodies, termed Tri-mAb, to a much lesser extent than the same tumor type located subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 56 publications
15
121
0
Order By: Relevance
“…Proof of this principle was recently provided by directly comparing the efficacy of immunotherapy on three orthotopic tumors versus their subcutaneous counterparts. This study showed that in addition to microenvironmental differences in immune cell profile and vascularity, orthotopic tumors are more immunosuppressive in nature and less sensitive to immunotherapy than subcutaneous tumors [188]. We have also learned that conventional anti-cancer therapies have both direct and indirect effects on the immune system (Figure 2).…”
Section: Discussionmentioning
confidence: 95%
“…Proof of this principle was recently provided by directly comparing the efficacy of immunotherapy on three orthotopic tumors versus their subcutaneous counterparts. This study showed that in addition to microenvironmental differences in immune cell profile and vascularity, orthotopic tumors are more immunosuppressive in nature and less sensitive to immunotherapy than subcutaneous tumors [188]. We have also learned that conventional anti-cancer therapies have both direct and indirect effects on the immune system (Figure 2).…”
Section: Discussionmentioning
confidence: 95%
“…Only a few groups took the effort to compare the ectopic and orthotopic tumors side by side, but their groundbreaking findings did not reach the mainstream of anticancer research. For instance, it has been demonstrated that renal, colon and prostate tumors respond to immunotherapy to a much lesser extent in the orthotopic setting compared to the subcutaneous location [5]. In analogy, renal carcinoma cells were described to be more resistant to treatment with doxorubicin when inoculated into kidneys compared to subcutaneous tumors [6].…”
Section: Short Communicationmentioning
confidence: 99%
“…Following intrarenal inoculation of Renca, a primary tumor forms in the kidney at the site of inoculation, resulting in the development of spontaneous lung metastases. 20 Since we had previously found that the use of anti-CD4 mAb was more effective than anti-CD25 or anti-FR4 at depleting Treg in BALB/c mice, 14 we treated mice bearing established SC or kidney Renca tumors (11 d) by intraperitoneal injection of anti-CD4 or control antibody on days 11, 12 and 13. All control-treated tumors grew progressively, but despite initial progression of tumors, the majority of SC tumors fully regressed following Treg depletion (Fig.…”
Section: Treg Depletion Using Anti-cd4 Eradicates Established Subcutamentioning
confidence: 99%
“…20 However, we did not assess in that study whether Treg could play a role in the immunosuppressive response occurring in IK Renca tumors.…”
Section: Introductionmentioning
confidence: 95%